Research on the Application of Traditional Color Elements in Modern Graphic Design (Journal of Global Arts Studies, 2024)
Background: As an important part of traditional culture, traditional color elements contain rich national emotions and cultural connotations, and are the source of inspiration and creativity for modern art design, reflecting the characteristics of modern design. Objective: Drawing on traditional color elements in modern graphic design, it discusses the application and value of using traditional color elements in modern graphic design so as to promote traditional Chinese culture, and then discusses the significance and value of the fusion of traditional color elements with modern graphic design, and the influence and use of modern graphic design. Methods: Starting from Chinese traditional colors, the use of Chinese traditional colors in modern graphic design is analyzed by means of the case study method. Results: Starting from the perspective of the value and role of traditional color in modern design, focusing on the penetration and integration of traditional color elements in modern design, aiming to enhance the aesthetic value of modern design and enrich the cultural connotation of modern design. Conclusion: The use of traditional Chinese color elements and graphics in modern graphic design has traditional philosophical thinking and cultural spirit, but also has the implication of modern design. Through in-depth discussion of its background, cultural connotation and application practice, it can provide designers with new creative ideas and methods, enrich the expression of modern graphic design, and promote the inheritance and innovative development of traditional culture.
Keywords: Color Aesthetics; Traditional Color; Color Culture; Modern Design